(706) Statistical Laboratory Exercise Book (part II) كتاب تمارين احصاء التجارب (الجزء الثاني) - Mahmoud, Moharram W. (معهد التخطيط القومى, 2024)
applications and examples of: Chi square analysis, including test of consistence-Test of goodness of fit < and test of independency ( contingency table) Analysis of variance two way factor Analysis of variance simple linear regression analysis multiple linear regression analysis curve linear regression analysis